31 medals garnered by UMP researchers in ITEX 2012 - UMP, PNC
Universiti Malaysia Pahang (UMP) researchers garnered 31 medals – five gold medals, 17 silver medals and nine bronze medals in the International Invention, Innovation and Technology Exhibition 2012 (ITEX) held in Kuala Lumpur Convention Centre on May 19, 2012 recently.